Changes in the composition of the RNA virome mark evolutionary transitions in green plants. Issue 1 (December 2016) - Mushegian, Arcady; Shipunov, Alexey; Elena, Santiago
Abstract Background The known plant viruses mostly infect angiosperm hosts and have RNA or small DNA genomes. The only other lineage of green plants with a relatively well-studied virome, unicellular chlorophyte algae, is mostly infected by viruses with large DNA genomes. Thus RNA viruses and small DNA viruses seem to completely displace large DNA virus genomes in late branching angiosperms. To understand better the expansion of RNA viruses in the taxonomic span between algae and angiosperms, we analyzed the transcriptomes of 66 non-angiosperm plants characterized by the 1000 Plants Genomes Project. Results We found homologs of virus RNA-dependent RNA polymerases in 28 non-angiosperm plant species, including algae, mosses, liverworts (Marchantiophyta ), hornworts (Anthocerotophyta ), lycophytes, a horsetailEquisetum, and gymnosperms. Polymerase genes in algae were most closely related to homologs from double-stranded RNA viruses leading latent or persistent lifestyles. Land plants, in addition, contained polymerases close to the homologs from single-stranded RNA viruses of angiosperms, capable of productive infection and systemic spread. For several polymerases, a cognate capsid protein was found in the same library. Another virus hallmark gene family, encoding the 30 K movement proteins, was found in lycophytes and monilophytes but not in mosses or algae. Conclusions The broadened repertoire of RNA viruses suggests that colonization of land and growth in anatomical complexity in land plants coincided with the acquisition of novel sets of viruses with different strategies of infection and reproduction.